FREQUENCY OF DAYTIME SLEEPINESS OF FACTORY WORKERS WORKING IN SHIFTS AND ITS EFFECT ON ANXIETY - Canan Birimoglu Okuyan (Rojan GÜMÜŞ, 2020)
Objective: This descriptive and cross-sectional study was conducted to examine the frequency of daytime sleepiness and its effects on anxiety in factory workers working in shifts. Methods: The population of the research consisted of 1052 workers working in two factories. The data were collected using the data collection form, Epworth Sleepiness Scale, and Beck Anxiety Inventory. Normally distributed data were presented as number, percentage, mean, and standard deviation. Independent samples t test and ANOVA were used in statistical analysis. Results: The mean Epworth Sleepiness Scale score of shift workers was 10.4 ± 4.2 and 42.8% had excessive daytime sleepiness. When the Epworth Sleepiness Scale scores and Beck Anxiety Inventory scores of the workers participating in the research were compared, it was determined that the daytime sleepiness levels of shift workers increased as anxiety risk increased, and the effect on vital characteristics was statistically significant (P < 0.05). Conclusion: Therefore, interventions, effective coping methods, and training strategies should be developed in order to improve the sleep quality, especially daytime sleep quality, and vital characteristics of shift workers.